Inelastic response spectra of self-centering structures with the flag-shaped hysteretic response subjected to near-fault pulse-type ground motions. Issue 4 (November 2021) - Dong, Huihui; Han, Qiang; Du, Xiuli; Cheng, Shoushan; He, Haifang
Many studies on the inelastic response spectra have mainly focused on structures with the conventional hysteretic behavior. However, for self-centering structures with the flag-shaped (FS) hysteretic behavior, the corresponding study is limited. The primary aim of this study is to investigate the inelastic response spectra of self-centering structures with FS hysteretic behavior subjected to the near-fault pulse-type ground motion. To this end, the smooth FS hysteretic model based on Bouc–Wen model is developed, and the characteristics of pulse-type ground motions are described in detail. It is found that the general features of inelastic response spectra of the FS model are sensitive to the acceleration-, velocity-, and displacement-sensitive spectral regions of the ground motion. The inelastic displacement, velocity, acceleration, and ductility factor spectra of the FS hysteretic model for pulse-type ground motions are much larger than those for ordinary ground motions, while the residual displacement spectra under the two types of ground motions are both very small due to its self-centering capacity. Moreover, the inelastic response spectra are affected by the ground motion characteristics and structural hysteresis behavior, especially the large pulse period and peak ground velocity (PGV) significantly increase the inelastic displacement, velocity, and acceleration spectra.